Clinical and electroencephalographic findings in acutely ill adults with non‐convulsive vs convulsive status epilepticus. (13th November 2013) - Pollak, L.; Gandelman‐Marton, R.; Margolin, N.; Boxer, M.; Blatt, I.
<x xml:space="preserve">Abstract</x> Background Non‐convulsive status epilepticus (NCSE) indicates a change in the mental state with no motor manifestations, being a clinical expression of prolonged epileptiform activity. In contrast to convulsive status epilepticus (CSE), no unified treatment recommendations have been proposed so far. We were interested to review the clinical and encephalographic characteristics in hospitalized patients with NCSE and CSE and compare their treatment and outcome. Patients and methods The electroencephalographic recording records of adult patients with electrographic status epilepticus were retrieved. Patients' clinical records were then analyzed. Results Fifty‐three patients with CSE and 25 patients with NCSE were identified. Background diseases, neuroimaging findings and complications were similar in CSE and NCSE. Anoxia was a more frequent etiological factor only for myoclonic SE. Patients with CSE presented more often with coma. The number of drugs used for treatment was similar, but anesthetics drugs were administered more frequently in patients with CSE. The 30‐day mortality rate was higher in myoclonic SE and generalized tonic‐clonic SE, but the outcome on discharge in terms of survival and recovery was comparable between CSE and NCSE. Conclusions The results of the present study show that the clinical parameters of NCSE in acutely ill patients do not substantially differ from those of patients with CSE. Moreover, despite more severe mental changes and the need for more anesthetic drugs for treatment of CSE, the final outcome did not differ between both groups. This might indicate that NCSE in acutely ill patients should be regarded as seriously as CSE.